Associations between Staphylococcus aureus Genotype, Infection, and In-Hospital Mortality: A Nested Case-Control Study. - Wertheim, H; van Leeuwen, W; Snijders, S; Vos, M; Voss, A; Vandenbroucke-Grauls, C; Kluytmans, J; Verbrugh, H; van Belkum, A (2005)
We screened 14,008 adult nonsurgical patients for Staphylococcus aureus nasal carriage at hospital admission and assessed them for invasive S. aureus disease and in-hospital mortality. Multilocus sequence typing was performed on endogenous invasive strains and nasal strains of matched asymptomatic carriers to investigate whether virulent clones could be identified in nasal carriers. Clonal complex (CC) 45 was significantly underrepresented (odds ratio [OR], 0.16 [95% confidence interval CI, 0.04-0.59]) and CC30 was overrepresented (not statistically significant) among invasive strains (OR, 1.91 [95% CI, 0.91-4.0]). The distribution of CCs of invasive S. aureus strains in noncarriers did not differ from that in carriers. Those infected with S. aureus strains belonging to a CC had higher mortality than those infected with strains not belonging to a CC (P<.05), which indicates the coevolution of S. aureus virulence and spread in humans.